Assessment of depression, anxiety and stress symptoms among patients with periodontal disease - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (Ektodermal Displazi Grubu, 2017)
The main objectives of the study are to assess the rate and severity of depression, anxiety and stress symptoms and to identify the possible association between these emotional disturbances with periodontal disease. This is a cross sectional study conducted on a sample of 159 patients with periodontal disease attending the periodontal clinic, Kulliyyah of Dentistry, International Islamic University Malaysia. The prevalence and severity of depressive, anxiety and stress symptoms were assessed among those patients by using the self-rating Bahasa Malaysia version of the Depression Anxiety and Stress Scale (DASS-21). The overall rate of depression, anxiety, and stress among patients was 18.9%, 36.5% and 19.5% respectively. Regarding the severity of the symptoms, it was found that 3.8%, 6.3 % and 2.5% of the patients had clinically significant depression, anxiety and stress respectively. Although patients with periodontitis had higher mean scores of depression, anxiety and stress than those with gingivitis but it was not statistically significant. Emotional disturbances in the form of depression, anxiety and stress are existing in high rates among patients with periodontal problem that require early detection and intervention.